2011
DOI: 10.1155/2011/252196
|View full text |Cite
|
Sign up to set email alerts
|

Askin's Tumor: A Dual Case Study

Abstract: Askin's tumor is a rare tumor arising from the chest wall. It is a subset of Ewing sarcoma characterized histologically by the presence of small round blue cells. It is a highly malignant tumor with guarded prognosis, which is dependent upon the extension of tumor at the time of diagnosis. A dual paper of Askin's tumors in young boys is being presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…According to classification of tumors of the nervous system, Askin's tumor is a member of the Ewing's sarcoma family of tumors/peripheral PNETs. The clinical occurrence of Askin's tumor is rare and only a limited number of cases have been documented (6)(7)(8)(9)(10)(11). The present study reported 11 cases of Askin's tumor, a relatively large sample size in terms of its incidence rate.…”
Section: Discussionmentioning
confidence: 56%
“…According to classification of tumors of the nervous system, Askin's tumor is a member of the Ewing's sarcoma family of tumors/peripheral PNETs. The clinical occurrence of Askin's tumor is rare and only a limited number of cases have been documented (6)(7)(8)(9)(10)(11). The present study reported 11 cases of Askin's tumor, a relatively large sample size in terms of its incidence rate.…”
Section: Discussionmentioning
confidence: 56%
“…El dolor local podría estar presente y disminuir en las noches pero no desaparecer completamente. Puede presentarse con parestesia local y raramente con fractura patológica o síntomas de metástasis relacionados [7]. Relacionado con el paciente presentado.…”
Section: Discussionunclassified
“…Algunas tiroides ectópicas linguales se manifiestan con cuadros obstructivos con disfagia y disfonía, hemorragia y función endócrina normal o alterada [1]. Se precisa realizar diagnóstico diferencial con hemangiomas, linfomas, fibromas, abscesos y tumores malignos de la lengua [7]. Casos de tiroides ectópica lingual son diagnosticados de forma incidental con métodos de imagen [3,6].…”
Section: Introductionunclassified